Analisis Faktor Yang Mempengaruhi Perilaku Menabung Anggota Misykat (Microfinance Syariah Berbasis Masyarakat) Daarut Tauhid Bogor - Rahmi Eka Putri; Hendri Tanjung; Mukhamad Yasid (Indonesian Journal of Islamic Economics and Business, 2021)
Saving money is very important tool to  improve the standard of living in the future. In addition, saving is also a way to deal with the risks caused by calamites that require large funds. Microfinance Insitutions can provide financial services to grassgroots.  DPU Daarut Tauhid formed the Misykat Program as an alternative solution to overcome the problems of the urban and rural poor. Misykat stresses the culture and paradigm of saving. This study goals are to observe the saving behavior of Misykat members (Community Based Sharia Microfinance), factors that influence members saving behaviour and the Misykat program influence to members saving behavior. Data analysis uses PLS-SEM Model using SmartPLS Versi 3.0. The results showed that : (1) Self-control has is a positive and insignificant at 0.129 towards saving behavior. (2) Attitude has a positive and insiginificant at 0.099 towards saving behavior. (3) Subjective norms has a negative and significant at -0.321 towards saving behavior. (4) Misykat Program has a positive and significant at 0.352 towards saving behavior.